Reductions in substance use-related parenting behaviors after participation in a digitally delivered parenting intervention - Amanda C. Trujillo; Samuel W. Rueter; Katherine A. Hails; Elizabeth A. Stormshak (Frontiers in Digital Health, 2026)
The Family Check-Up Online (FCU-O) fills a unique gap in family prevention by providing digital, accessible content to support substance-involved parents outside of residential treatment settings to reduce the impact of substance use on parenting. We examined whether parents reported reductions in coping motivations for substance use (CM) and substance use-related parenting interference (PI) after completing the FCU-O substance use module. We further explored whether baseline substance use-related risk was associated with differential change in parenting outcomes over time. Method Participants were parents ( N = 180) of 1.5–5-year-old children assigned to the FCU-O within a randomized controlled trial and self-reported CM and PI via a pre- and post-assessment embedded within the app. We conducted linear mixed-effects models for each outcome. Results Analyses revealed a significant effect of time for CM ( β = −0.46, SE = 0.22, t = −2.13, p = 0.035), but not for PI ( β = 0.05, SE = 0.18, t = 0.28, p = 0.783). Exploratory moderation analyses indicated that baseline substance use risk was significantly associated with higher levels of CM and PI at baseline, however, risk did not significantly moderate change over time for either CM or PI ( p > 0.17 for each). Discussion Findings suggest that parents endorsed less frequent CM after completing the FCU-O substance use module, while PI remained stable. These findings provide preliminary support for the FCU-O in improving substance-related coping behaviors and can guide future efforts to support substance-involved parents in parenting effectively and safely.